The Impact of Income Inequality on Economic Growth in Vietnam: An Empirical Analysis - Le, Quoc Hoi; Nguyen, Hoai Nam (Asian Economic and Financial Review, 2019)
This paper tests the theoretical models proposed in the literature to explain the impact of income inequality on economic growth at the provincial level in Vietnam. The results show a weak direct link between initial inequality and subsequent economic growth. However, income inequality affects economic growth through several channels. There is strong empirical support for the negative impact of inequality on growth via the education/fertility channel. The data also supports capital market imperfection. By contrast, there appears to be less empirical support for explanations based on the distribution channel. The results indicate that the channels through which income inequality leads to higher economic growth are offset by the opposing channels through which inequality harms growth. Based on the findings the paper proposes policy measures that could be implemented by the government to narrow the gap between the rich and the poor in Vietnam and ensure a fairer distribution of economic resources.